1998
DOI: 10.1002/jlb.63.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation in the immune system: all roads lead to AP-1

Abstract: The mechanisms regulating the development and function of the immune system are diverse and complicated. The signaling pathways and target genes that become activated upon cell-surface stimulation are currently being defined, and transcription factor activator protein 1 (AP-1) is proving to be an important regulator of nuclear gene expression in leukocytes. In vitro and in vivo studies have demonstrated that AP-1 expression is induced after a diverse range of stimuli and that AP-1 contributes to the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
257
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(274 citation statements)
references
References 204 publications
11
257
0
4
Order By: Relevance
“…Interestingly, Ets and AP-1 binding sites occur in a large number of promoter/enhancer elements, and functional cooperation between Ets and AP-1 is critical for controlled expression of many genes, including cytokines (47,51,52). It is notable, though, that AP-1 is not only activated in T cells following TCR cross-linking, but can be a consequence of a broad spectrum of stimuli in a variety of cells (53). Thus, it is still possible that under the appropriate circumstances activation of this pathway could lead to the expression of Jak3 in nonlymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ets and AP-1 binding sites occur in a large number of promoter/enhancer elements, and functional cooperation between Ets and AP-1 is critical for controlled expression of many genes, including cytokines (47,51,52). It is notable, though, that AP-1 is not only activated in T cells following TCR cross-linking, but can be a consequence of a broad spectrum of stimuli in a variety of cells (53). Thus, it is still possible that under the appropriate circumstances activation of this pathway could lead to the expression of Jak3 in nonlymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 Triggering of this conserved TLR signal transduction converges in the activation of the transcription factors nuclear factor (NF)-kB and AP-1, which control the expression of key immunoregulatory genes. 3,4 At first, binding of ligands to TLRs recruits a central adaptor, MyD88, shared by almost all TLRs, with the exception of TLR3. Hereupon, MyD88 associates with members of the interleukin-1 (IL-1) receptor-associated kinase (IRAK) family.…”
Section: Introductionmentioning
confidence: 99%
“…20 Homodimers of c-Jun or heterodimers of c-Jun and c-Fos modulate several biological responses by binding to the DNA consensus sequence TGA(C/G)TCA (12-o-tetradecanoylphorbol 13-acetate-responsive element of TRE) found in the promoter region of several genes. 21 There is ample evidence that the activity of AP-1, especially that of c-Jun, is essential for cell proliferation and differentiation. Recently, it has been suggested that certain components of AP-1 may also be involved in programmed cell death (PCD).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that certain components of AP-1 may also be involved in programmed cell death (PCD). 20,21 However, the available information is contro-versial, showing a scenario where AP-1 activity is essential for cells to undergo apoptosis under certain conditions such as cytokine withdrawal, 22 but may not be linked to cell death in the case of TNF-a or Fas-induced apoptosis. 23,24 In the present study we investigated whether binding of Gal-1 to mature T cells triggers activation of AP-1 and modulates expression of the c-Jun proto-oncogene.…”
Section: Introductionmentioning
confidence: 99%